2007
DOI: 10.1111/j.1742-1241.2006.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glargine group-start sessions in patients with type 2 diabetes as a strategy to deliver the service

Abstract: Improving glycaemic control in patients with type 2 diabetes reduces microvascular complications. The national service framework for diabetes and the new general medical service contract have been aiming to direct more focus on improving HbA1c. These measures have resulted in increasing number of patients being initiated on insulin therapy, which increases the workload of diabetes specialist nurses (DSNs). Initiating insulin on a one-to-one basis is time consuming. As a result DSN-led insulin group-start sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Although the end-of-study use of concomitant OADs did not change substantially from baseline (43% taking sulfonylureas and 43% metformin), the dose of insulin glargine was comparatively low at 16.0 IU per day. By contrast, in a UK-based study of basal insulin glargine treatment initiated within routine secondary care, HbA1c decreased by 1.1% after 12 months, but this was associated with a mean weight gain of 4.0 kg and hypoglycemia in 24% of patients [30]. The most notable difference in the UK study compared to Schreiber et al and Lechtleiner et al was the median endof-study daily insulin dose of 40 IU (0.49 IU/kg).…”
Section: Basal Insulin Glargine Regimens In Routine Clinical Practicementioning
confidence: 48%
See 2 more Smart Citations
“…Although the end-of-study use of concomitant OADs did not change substantially from baseline (43% taking sulfonylureas and 43% metformin), the dose of insulin glargine was comparatively low at 16.0 IU per day. By contrast, in a UK-based study of basal insulin glargine treatment initiated within routine secondary care, HbA1c decreased by 1.1% after 12 months, but this was associated with a mean weight gain of 4.0 kg and hypoglycemia in 24% of patients [30]. The most notable difference in the UK study compared to Schreiber et al and Lechtleiner et al was the median endof-study daily insulin dose of 40 IU (0.49 IU/kg).…”
Section: Basal Insulin Glargine Regimens In Routine Clinical Practicementioning
confidence: 48%
“…Filled diamonds indicate prestudy HbA1c, filled squares indicate mean post-study HbA1c for insulin glargine. Studies 1-3 correspond to basal insulin plus OAD regimens in clinical practice [26,28,30], study 4 corresponds to the Rosenstock meta-analysis of randomized trials of insulin glargine [17]. Standard deviation (SD) bars correspond to end-of-study HbA1c, and the shaded area corresponds to SD surrounding the change in HbA1c concluded from the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving quality of life is the ultimate outcome for any therapy, and treatment satisfaction is associated with regimen adherence 8 and with consequent clinical outcomes. [8][9][10][11] Use of inhaled Technosphere insulin has been shown to improve perceptions of insulin therapy in insulin naïve patients. 12 But to date there are no reports comparing the effects of a regimen including inhaled Technosphere insulin and a comparator insulin regimen on patient-reported outcomes (PRO) such as HRQoL and treatment satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Improving quality of life is the ultimate outcome for any therapy, and treatment satisfaction deserves attention because it is associated with regimen adherence 10 and with consequent clinical outcomes. [10][11][12] A comprehensive assessment of patient-reported outcomes (PRO) should include consideration of (1) general health-related quality of life (HRQOL), (2) diabetes-related worries, (3) perceptions of insulin therapy, and (4) perceptions of the insulin delivery system. All of these PRO were studied in a double-blind, randomized clinical trial of active inhaled Technosphere insulin versus placebo inhaled Technosphere insulin.…”
Section: Introductionmentioning
confidence: 99%